Response of Growth and Yield of Sweet Corn (Zea mays saccharata Sturt) to Giving Tofu Liquid Waste and Chicken Manure Fertilizer - Heirin Simon (Central Research Institute For Agriculture, 2023)
This study aims to determine the response of growth and yield of Sweet corn crops (Zea mays saccharata Sturt) on the provision of liquid waste tofu and chicken manure. This research was arranged by using Randomized Block Design with treatments, namely: Control (P0), liquid waste tofu 300 ml (P1), liquid waste tofu 600 ml (P2), chicken manure (P3), liquid waste tofu 300 ml + chicken manure (P4), liquid waste tofu 600 ml + chicken manure (P5) with 4 replications. The variables observed in this study consist of; plant height, number of leaves, number of cobs, cob weight and wet weight of the plant. Data were analyzed by using variance test (Anova) followed by Duncan 5% test. The results showed that the liquid waste treatment of 600 ml + chicken manure can increase the plant height, the number of leaves, the number of cobs, the weight of the cob and the wet weight of the plant. The best crop yields were found in the treatment of liquid waste of 600 ml + manure (P5) because it was able to increase plant height 61.20%, leaves 40.16%, cobs 79%, cob weight 564,74%, wet weight 163, 83% compared with control treatment (P0).